A Note on Physical and Mechanical Properties of Tetrameles nudiflora (Maina) from Assam - Jain, J. D.; Gupta, V. K. (Indian Forester, 1979)
Physical and mchanical properties bave been evaluated and reported in green, air-dry and kilo-dry conditions based on small clear specimens obtained from five logs of Tetrameles nudiflora (Maina), received from Dhansiri Valley Division, Assam. The results obtained have been compared with standard Teak. It is found that values are much lower than standard Teak in general. Expected values based on strength specific gravity formulae have also been reported for comparison. Suitability indices have also been reported.